Key Success Factors of Thai OTOP - Boonyarasai, Phathamon; Jongsureyaphas, Chatrudee (Journal of Management Science Chiangrai Rajabhat University, 2018)
The objective of this research were to study key success factors of Thai OTOP, to analyze the causal confirmatory factors affecting the success of Thai OTOP and to study causal relationship with the structural equation model. The samples using in this study included 355 five stars OTOP entrepreneurs selected by multi stage sampling. The instrument was a questionnaire. Data was analyzed by using computer program in calculating the basic statistics, and confirmatory factor analysis for testing congruence between factor structure model in key success factors of Thai OTOP and the empirical data. The variables as major factors affecting success of Thai OTOP consisted of 5 major variables as follows: 1) the accounting and financial, 2) the production and marketing, 3) the creativity the, 4) entrepreneurship, and 5) the innovation. All of these 5 major factors had to perform through variables with 14 indicators of production and marketing factor, 9 indicators of accounting and financial factors, 2 indicators of creativity factor, 3 indicators of entrepreneurship factor, and 3 indicators of innovation factor. Five major key success factors of Thai OTOP were obtained. There were; 1) the accounting and financial, 2) the production and marketing, 3) the creativity, 4) the entrepreneurship and, 5) the innovation. These five major factors were performed through 31 indicators. The weights loaded of the five factors were 1) 0.557 for the accounting and financial, 2) 0.533 for the production and marketing, 3) 0.202 for the creativity, 4) 0.192 for the innovation, and 5) 0.025 for the entrepreneurship. The goodness of fit of structural relationship model showed its consistency with the empirical data (Chi-Square = 474.372, df = 434, p = 0.088, TLI = .990, CFI = .993, RMSEA = .016, HOELTER = 361). In this research, in was concluded that the statistical analysis results confirmed the research hypotheses.